KKN 168 UMD: Community-based Empowerment in Kedungjajang Village through Pawon Urip, Ecobrick, and Compost Programs: KKN 168 UMD: Pemberdayaan Masyarakat Desa Kedungjajang melalui Program Pawon Urip, Ecobrick, dan Kompos - Cahyono, Bagus Dwi; Wijaya, Umar Agusta; Putri Gesika, Amanda Amelia; Meganatalia, Dessy Rosantika; Afrohatin, Hanin; Pradana, Ardyo Andy; Febrianto, Syarif Nur; Istanto, Hildania Putri; Purwadi, Dika Wijaya Kusuma; Badri, Ahmad; Tamma, Anggun Arsyada Brilliant; Primaputra, Damar Raharjo; Nurhidayah, Adhisa (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2023)
KKN is a form of student service to the community. One of the villages that became the target of the University of Jember's KKN is Kedungjajang Village in Lumajang Regency. The KKN 168 work program in Kedungjajang Village this time raised the theme of food security and environmental awareness. The program developed by our team is the Pawon Urip program so that the community can utilize the empty land around the house to plant toga plants which can be used for daily cooking ingredients. In addition, this KKN 168 program also processes household waste, both organic and inorganic waste, to be used as eco-bricks and compost. This can build public awareness of the surrounding environment so that the environment becomes clean and the waste that is usually useless can be reused. The activities of making a Pawon Urip garden, training on making compost from food scraps, and making eco-brick are one of the activities with the aim of making the people of Kedungjajang Village aware and concerned about the environment.